When machine learning extrapolates in space: How local data shape spatial transferability - Camille Portes; Dino Ienco; Edith Gabriel (Spatial Statistics, 2026)

Sequential area interaction sampling for early plant disease detection - François d’Alayer; Edith Gabriel; Samuel Soubeyrand (Spatial Statistics, 2026)

Molecular identification of the edible rock scallop, Spondylus limbatus (Bivalvia: Spondylidae) from the southwestern Gulf of California - Luis Gabriel Aguilar-Estrada; Nataly Quiroz-González; María Edith Ponce-Márquez; Elisa Serviere-Zaragoza; Sergio Scarry González-Pelaez; Martha Reguero (Molluscan Research, 2026)

Singular Geological Evidence, Historical Record and Socio-Economic Consequences of Recent Coastal Erosion and Future Sea Level Rise on Tourist Beaches: A Case Study from Southwestern Spain - Tatiana Izquierdo; Manuel Abad; Francisco Ruiz; Luis Miguel Cáceres; Joaquín Rodríguez Vidal; Fernando Muñiz; María Luz González-Regalado; Carlos Neto de Carvalho; Antonio Toscano; Paula Gómez; Verónica Romero; Gabriel Gómez; et al. (Journal of Earth Science, 2026)

Hematological and Biochemical Outcomes of Leishmania Infantum Infection in the South American Coati (Nasua nasua) in an Endemic Area of Visceral Leishmaniasis in Central Western Brazil - Gabriel Carvalho de Macedo; André Luiz Rodrigues Roque; Filipe Martins Santos; Wanessa Teixeira Gomes Barreto; Carina Elisei de Oliveira; William Oliveira de Assis; Grasiela Edith de Oliveira; Andreza Castro Rucco; Gisele Braziliano de Andrade; Alanderson Rodrigues da Silva; Nayara Yoshie Sano; Julia Gindri Bragato Pistori; et al. (Acta Parasitologica, 2026)

Implementation of an Educational Intervention for Gastric Cancer Awareness in the General Population in CELAC and Europe: A Strategy Proposed by the LEGACy Consortium - Juan Antonio Carbonell-Asins; Elena Jiménez-Martí; Sergio Romero; Eduardo García; Ana Miralles-Marco; Beatriz Lopez; Marisol Huerta; Carmelo Caballero; Hugo Boggino; Cinthia Gauna; Olga Beatriz Acevedo-Funes; Gabriel Benitez Nuñez; et al. (Journal of Cancer Education, 2025)
Gastric cancer (GC) has a poor prognosis. The LEGACy consortium has been established to enhance GC outcomes though improved primary and secondary prevention strategies. We performed an educational intervention study using an online module to disseminate knowledge about GC risk factors and symptoms to the general population. Participants were recruited through various media channels and were exposed to an online questionnaire to assess their knowledge, before and after the educational intervention. The educational intervention included an informative brochure and a short video providing essential information about GC. Primary outcome was to evaluate the overall knowledge (global score) before and after the intervention. A total of 1034 participants were evaluated before the intervention. Of those, 866 also completed the short-term and 362 the long-term questionnaire after the intervention, respectively. On a scale of 0 to 17, the baseline global score mean was 9.4 (3.2). Results showed an increase in the average global knowledge score by 1.80 (95% CI: 1.63–1.96, p < 0.001) and 1.81 (95% CI: 1.65–1.96, p < 0.001) points after completing the short and long-term questionnaires compared to the baseline respectively for all individual questions ( p < 0.05). This interventional study showed significantly improved knowledge in most domains on GC risk factors, signs, and symptoms which could be a useful strategy for promoting cancer prevention. ClinicalTrials.gov Identifier: NCT04019808.

Opportunities to better integrate inland fish and fisheries in multilateral environmental agreements - Abigail J. Lynch; Devin Bartley; T. Douglas Beard, Jr.; Gabriel Borba; Steven J. Cooke; Ian G. Cowx; Vittoria Elliott; Holly Embke; Edith Gondwe; Zeb Hogan; Jonathan G. Low; Jamie C. Madden; et al. (Environmental Science & Policy, 2025)

A marked sequential point process for disease surveillance: Modeling and optimization - François d’Alayer; Edith Gabriel; Samuel Soubeyrand (Spatial Statistics, 2025)

Molecular identification of the Edible Chiton, Chiton articulatus (Polyplacophora: Chitonidae) from Mexican Tropical Pacific - Luis Gabriel Aguilar-Estrada; Nataly Quiroz-González; Maria Edith Ponce-Márquez; Ivette Ruíz-Boijseauneau (Molluscan Research, 2025)

Integrating plasmasphere, ionosphere and thermosphere observations and models into a standardised open access research environment: The PITHIA-NRF international project - Anna Belehaki; Ingemar Häggström; Tamas Kiss; Ivan Galkin; Anders Tjulin; Mária Miháliková; Carl-Fredrik Enell; Gabriel Pierantoni; Yin Chen; Gergely Sipos; Sean Bruinsma; Viviane Pierrard; et al. (Advances in Space Research, 2025)

Hematology and biochemistry of South American coatis Nasua nasua (Carnivora: Procyonidae) inhabiting urban fragments in Midwest Brazil: differences according to intrinsic features and sampling site - Gabriel Carvalho de Macedo; Wanessa Teixeira Gomes Barreto; William Oliveira de Assis; Andreza Castro Rucco; Filipe Martins Santos; Grasiela Edith de Oliveira Porfírio; Nayara Yoshie Sano; Julia Gindri Bragato Pistori; Gisele Braziliano de Andrade; Heitor Miraglia Herrera (European Journal of Wildlife Research, 2023)

Mapping the intensity function of a non-stationary point process in unobserved areas - Edith Gabriel; Francisco Rodríguez-Cortés; Jérôme Coville; Jorge Mateu; Joël Chadœuf (Stochastic Environmental Research and Risk Assessment, 2023)

Brucellosis in the Brazilian Pantanal wetland: threat to animal production and wildlife conservation - Gabriel Carvalho de Macedo; Heitor Miraglia Herrera; Grasiela Edith de Oliveira Porfírio; Filipe Martins Santos; William Oliveira de Assis; Gisele Braziliano de Andrade; Wesley Arruda Gimenes Nantes; Javier Hermoso de Mendoza; Pedro Fernández-Llario; Carina Elisei de Oliveira (Brazilian Journal of Microbiology, 2022)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Dispersal and resistance to starvation in Raoiella indica (Acari: Tenuipalpidae) - José Ramírez-López; Gabriel Otero-Colina; Edith Guadalupe Estrada-Venegas; Claudia Ballesteros-Barrera; Hermilo Jorge Quero-Rico (Experimental and Applied Acarology, 2020)

Integrating expert knowledge and ecological niche models to estimate Mexican primates’ distribution - Edith Calixto-Pérez; Jesús Alarcón-Guerrero; Gabriel Ramos-Fernández; Pedro Américo D. Dias; Ariadna Rangel-Negrín; Monica Améndola-Pimenta; Cristina Domingo; Víctor Arroyo-Rodríguez; Gilberto Pozo-Montuy; Braulio Pinacho-Guendulain; Tania Urquiza-Haas; Patricia Koleff; et al. (Primates, 2018)

Herbicides in vineyards reduce grapevine root mycorrhization and alter soil microorganisms and the nutrient composition in grapevine roots, leaves, xylem sap and grape juice - Johann G. Zaller; Clemens Cantelmo; Gabriel Dos Santos; Sandrina Muther; Edith Gruber; Paul Pallua; Karin Mandl; Barbara Friedrich; Ingrid Hofstetter; Bernhard Schmuckenschlager; Florian Faber (Environmental Science and Pollution Research, 2018)

Differential termiticidal effects of Spondiathus preussii Engl. var preussii extracts on Vitex doniana wood - Gabriel Adetoye Adedeji; Adekunle Tajudeen Oladele; Adedapo Ayo Aiyeloja; Taiwo Olayemi Elufioye; Edith Omasirichi Elenwo (Journal of the Indian Academy of Wood Science, 2018)

A. Baddeley, E. Rubak, R. Turner: Spatial Point Patterns: Methodology and Applications with R - Edith Gabriel (Mathematical Geosciences, 2017)

Salt Glands in the Poaceae Family and Their Relationship to Salinity Tolerance - Gabriel Céccoli; Julio Ramos; Vanesa Pilatti; Ignacio Dellaferrera; Juan C. Tivano; Edith Taleisnik; Abelardo C. Vegetti (The Botanical Review, 2015)

Air quality monitoring system using lichens as bioindicators in Central Argentina - Cecilia Estrabou; Edith Filippini; Juan Pablo Soria; Gabriel Schelotto; Juan Manuel Rodriguez (Environmental Monitoring and Assessment, 2011)

Evaluating the sampling pattern when detecting Zones of Abrupt Change - Edith Gabriel; Denis Allard (Environmental and Ecological Statistics, 2008)

Molecular characterization of tobacco ribonucleotide reductase RNR1 and RNR2 cDNAs and cell cycle-regulated expression in synchronized plant cells - Marie-Edith Chabouté; Bruno Combettes; Bernadette Clément; Claude Gigot; Gabriel Philipps (Plant Molecular Biology, 1998)